Nitrogen applied in okra under non-tightness grown and residual fertilization. - CARDOSO, M. O. (2012)
The aim of this study was to evaluate, in the Amazonian rainy season, the effect of nitrogen applied in okra under non-tightness grown and residual fertilization.